(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This scientific article analyzes the experience of using technological equipment in the production of building materials. The role of technological equipment in production efficiency, product quality and environmental safety is analyzed in depth. The results achieved through the integration of digitization, automation, energy saving and artificial intelligence into the industry are highlighted. Innovative approaches are substantiated based on comparative analysis with foreign experiences.